Introduction: Symposium on ‘Convicting the Innocent - Garrett, Brandon L. (2012)
Examining what went wrong in the first 250 DNA exonerations was a sobering occupation, and I describe what I found in my book Convicting the Innocent, published by Harvard University Press in 2011. Still more haunting is the question of how many other wrongful convictions have not been uncovered and will never see the light of day. The New England Law Review has brought together a remarkable group of scholars who have each made leading contributions to the study of wrongful convictions from different disciplines and scholarly perspectives: Simon Cole, Deborah Davis, Gisli H. Gudjonsson, Richard Leo, and Elizabeth Loftus. Each has done ground-breaking work focusing on evidence in criminal investigations and prosecutions, looking beyond just what we know from the wrongful convictions that do come to light. This Symposium issue returns the focus to research that can tell us more about the causes of wrongful convictions, and in this introduction I try to do justice to their remarkable contributions